2015
DOI: 10.12659/msm.893745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cnidium Lactone on Serum Mutant P53 and BCL-2/BAX Expression in Human Prostate Cancer Cells PC-3 Tumor-Bearing BALB/C Nude Mouse Model

Abstract: BackgroundCnidium lactone is a natural coumarin compound that can inhibit a variety of cancer cell proliferation and induce cancer cell apoptosis. This experiment investigated the effect of cnidium lactone on molecular marker expression in prostate cancer nude mice to study its effect in inducing apoptosis.Material/MethodsWe randomly and equally divided 30 male BALB/C nude mice inoculated with human prostate cancer cells PC-3 into a negative control group, a cyclophosphamide group (500 mg/Kg), and cnidium lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…4e, j ). In the Bcl-2 protein family, the Bcl-2/Bax ratio has been shown to affect apoptosis induction [ 26 , 27 ]. Our data indicated that USP37#2 shRNA combined with cisplatin induced the cell apoptosis with an underlying decrease in the Bcl-2/Bax ratio.…”
Section: Resultsmentioning
confidence: 99%
“…4e, j ). In the Bcl-2 protein family, the Bcl-2/Bax ratio has been shown to affect apoptosis induction [ 26 , 27 ]. Our data indicated that USP37#2 shRNA combined with cisplatin induced the cell apoptosis with an underlying decrease in the Bcl-2/Bax ratio.…”
Section: Resultsmentioning
confidence: 99%
“…One of the major determinants of cell survival is the balance between the anti-apoptotic and pro-apoptotic members of the Bcl-2 family [18]. In the Bcl-2 protein family, pro-apoptotic factor Bax and anti-apoptotic factor Bcl-2 are the active regulators and effectors, and the ratio between Bcl-2 and Bax (Bcl-2/Bax) affects apoptosis induction [19,20]. In the meantime, we evaluated Bcl-2 and Bax after HMGB3 knockdown and found that Bax increased and Bcl-2 reduced when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of Bcl-2 and inhibition of Bax expression are closely correlated with anti-apoptosis/apoptosis imbalance of glioma cells. 23 This study demonstrated that after MP/VC treatment, the proliferation of glioma cells was remarkably inhibited, enhancing tumor cell apoptosis, decreasing mRNA/protein expression of Bcl-2 while increasing Bax mRNA or protein expression. Meanwhile, the expression of caspase-3 and its endogenous substrate, cleavage of PARP, were enhanced in our study.…”
Section: Discussionmentioning
confidence: 70%